A Novel Diagnostic Predictive Model for Idiopathic Short Stature in Children - Yuan, Jinghong; Du, Zhi; Wu, Zhiwen; Yang, Yanqin; Cheng, Xigao; Liu, Xijuan; Jia, Jingyu (Frontiers in Endocrinology, 2021)
Objective: Idiopathic short stature (ISS), an endocrine-related disease, is difficult to diagnose. Previous studies have shown that many children with some inflammation-related diseases often have short stature, but whether inflammation is the underlying mechanism of ISS has not been studied. Here, we attempt to explore the role of inflammation in the occurrence and development of ISS and to demonstrate an available clinical diagnostic model of ISS. Methods: Frozen serum samples were collected from ISS patients (n = 4) and control individuals (n = 4). Isobaric tags for relative and absolute quantitation (iTRAQ) combined with LC-MS/MS analysis were applied to quantitative proteomics analysis. Then bioinformatics analysis including functional enrichment and network analyses were performed and the crucial proteins were detected by Molecular Complex Detection (MCODE). Furthermore, serum levels of two selected proteins were measured by ELISA between ISS patients (n = 80) and controls (n = 80). In addition, experiments in vitro were used to further explore the effects of crucial proteins on endochondral ossification. Results: A total of 437 proteins were quantified and 84 DEPs (60 upregulated and 24 downregulated) were identified between patients with ISS and controls. Functional enrichment analysis showed that the DEPs were primarily enriched in blood microparticle, acute inflammatory response, protein activation cascade, collagen-containing extracellular matrix, and platelet degranulation, etc. According to the results of the top 10 fold change DEPs and MCODE analysis, C1QA and C1QB were selected to further experiment. The expression level of C1QA and C1QB were validated in serum samples. Based on the logistic regression analysis and ROC curve analysis, we constructed a novel diagnostic model by serum levels of C1QA and C1QB with a specificity of 91.2% and a sensitivity of 75% (AUC = 0.900, p <0.001). Finally, the western blotting analysis confirmed the expression levels of OCN, OPN, RUNX2, and Collagen X were downregulated in chondrocytes, and the outcome of Collagen II was upregulated. Conclusion: Our study is the first to demonstrate the significant role of inflammation in the development of ISS. In addition, we identify that C1QA and C1QB as novel serum biomarkers for the diagnosis of ISS.